Mini-review: The health benefits and applications of allicin - Chen, Ke-Qian; Lei, Hai-Bo; Liu, Xiang; Cao, Wen-Jing (Frontiers in Pharmacology, 2025)
Garlic is a perennial plant with a long history of cultivation and medicinal use. As a valuable food additive and spice, garlic contains many nutrients and chemicals. Allicin is a key bioactive organosulfur metabolite derived from garlic bulbs. In recent years, more and more scientists have carried out research on it. This article reviews the health benefits and applications of allicin. Meanwhile, we also discussed the limitations of relevant research on allicin and look forward to the future prospects of allicin. We found that allicin is a valuable metabolite in medicine and the food field. With the deepening of allicin research, the application of allicin will have a broader prospect.